The retail store managers' role: Evidence from Greece - Antonios Zairis (International Journal of Business Science & Applied Management (IJBSAM), 2013)
Despite the fact that the retail manager's role is determinant for a store's performance, and there is abundant wisdom about how to be an outstanding manager or what are the characteristics of a successful retail manager, there is no detailed description about the store managers' role or their actual work. Furthermore, the continuous developments in the retail sector have established different roles and created higher levels of responsibility for store managers. The aim of the present paper is to empirically investigate the role of retail store managers in Greece and identify any potential differences in terms of personal characteristics, tasks and various job-related factors. For the purposes of this research a survey was conducted focusing on the sectors of apparel/footwear and food, in an attempt to explore any potential differences within the two divisions. The results revealed the profile of the Greek store managers (male, over the age of 40, with a secondary level of education and more than five years of work experience) and their multi-factor role. The three major roles that they perform were labeled as: sales oriented, supervisor, and customer experience oriented. The research also indicated that the two most popular sub-sectors in the Greek retail industry employ different profile managers. The issues of work experience, job satisfaction and security were also analysed.
Keywords: 650; store managers; retail; role; Greece; job satisfaction